Connecting postsecondary quality of life to promises of IDEA: an issue of educational equity - Heiman, Margaret (Nikki) (Kansas State University, 2024)
This mixed methods study on postsecondary outcomes for individuals with disabilities focused on the experiences of young adults with intellectual and developmental disabilities (IDD) and significant disabilities from their perspective. The research questions include understanding their overall quality of life (QOL), the supports, services, and experiences they received during Individuals with Disabilities Education Act (IDEA) Part B, and how these experiences contributed to their current QOL as young adults. The study used a constructivist and pragmatic worldview, focusing on the importance of understanding IDEA supports and services from the perspective of individuals who received them. The research design involved collecting both qualitative and quantitative data, with the qualitative phase informed by the quantitative phase. The research was completed in two phases, with the first phase focusing on the participants' overall QOL rating using the Wisconsin Quality of Life Survey and the second phase on the qualitative aspects of their QOL. The research provides a more comprehensive understanding of the experiences and perspectives of young adults with disabilities in postsecondary education. Ultimately, the study participants emphasized the challenges they face as young adults transitioning from IDEA Part B to adulthood. They stressed the importance of social networks and the need for individualized education plan (IEP) teams to support social nuance and meaningful connections throughout all their IDEA journey. The findings also bring to light the need for specialized ages 18-21 special education services, which are crucial for cultivating employability skills and life competencies. The findings in this study highlight the need for bridging the gap between policy and practice, which would empower young adults with disabilities to chart their own destinies with autonomy and agency. By bridging this gap, we can better create a future where individuals with disabilities are not just survivors but architects of their destinies, with dignity, in a place where opportunities abound.
Keywords: Special education; Disability; Intellectual disability; Quality of life; Postsecondary outcomes